Principles of International Investment Law - Dolzer, Rudolf (Oxford University Press, 2008)
This book outlines the principles behind the international law of foreign investment. The main focus is on the law governed by bilateral and multilateral investment treaties. The book traces the purpose, context and evolution of the clauses and provisions characteristic of contemporary investment treaties, and analyzes the case law interpreting the issues raised by standard clauses. Particular consideration is given to broad treaty-rules whose understanding in practice has mainly been shaped by their interpretation and application by international tribunals